OAM-based reconfigurable doppler shifts enable PAPR reduction for multi-carrier doppler diversity - Zhao, Yufei (2023)
Orbital Angular Momentum (OAM) is recognized as an intrinsic property of Electro-Magnetic (EM) waves. The orthogonality between multiple OAM modes is usually exploited to improve the spectral efficiency and transmission rate in wireless communications. In a recent study, we discovered that even when the transceivers are stationary, a specific spatial Doppler shift can be generated by rotating the wavefront structure of the OAM helical beams. Furthermore, arbitrary integer rotational OAM Doppler shifts can be realized flexibly by using the recently popular digital encoding metasurfaces. The artificial Doppler signals can be widely used in various wireless transmission scenarios, such as Doppler spoofing stealth, Doppler index modulation, and frequency-hopping channels. As a specific example, this paper demonstrates that in the discontinuous Orthogonal Frequency Division Multiplexing (OFDM) systems, the Peak to Average Power Ratio (PAPR) degradation caused by superposition of multi-carrier signal for additional Doppler diversity can be greatly alleviated by means of the OAM-based reconfigurable Doppler shifts.